Rozstrzyganie o prawie do mieszkania po orzeczeniu rozwoju - Sokołowski, Tomasz (Wydział Prawa i Administracji UAM, 1989)
A common right to an appartment vested in divorced spouses is the example of relations the. regulation of which requires a further court decision in a post- -divorce period. The article discusses, the problems of allocation of the right of tenancy to one of the divorced spouses and the issue of admissibility of eviction of one of the divorced spouses from their common apartment. The author is in favour of court proceedings based on Art. 58 § 2 of the Family and Guardianship Code in matters analysed in his contribution. Besides, he is against the tendency trying to place the above decisions with local organs of housing administration.
Decisions concerning the right to an apartment after divorce